2020
DOI: 10.3390/diagnostics10090724
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Migraine in Patients with Temporomandibular Disorder: A Longitudinal Follow-Up Study Using a National Health Screening Cohort

Abstract: Background: The aim of this study was to investigate the association between temporomandibular disorder (TMD) and migraine through a longitudinal follow-up study using population data from a national health screening cohort. Methods: This cohort study used data from the Korean National Health Insurance Service-Health Screening Cohort from 2002 to 2015. Of the 514,866 participants, 3884 TMD patients were matched at a 1:4 ratio with 15,536 control participants. Crude models and models adjusted for obesity, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…31,32 In some of these studies, it was stated that individuals with temporomandibular joint disorder (TMD) and occlusion problems have a higher risk of migraine. 33,34 In addition, depression and anxiety are also known to be associated with TMD disorders. 35 Depression and anxiety symptoms have also been reported as common symptoms in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In some of these studies, it was stated that individuals with temporomandibular joint disorder (TMD) and occlusion problems have a higher risk of migraine. 33,34 In addition, depression and anxiety are also known to be associated with TMD disorders. 35 Depression and anxiety symptoms have also been reported as common symptoms in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…TMD was defined as a diagnosis of K07.6 (temporomandibular joint disorders). Participants who visited the clinic ≥ 2 times and were diagnosed with code K07.6 were included ( 19 ). The date of outcome event (diagnosis of TMD) was defined as the date of initial diagnosis of TMD.…”
Section: Methodsmentioning
confidence: 99%
“…The participants had been diagnosed under the diagnostic code for TMJD (ICD-10: K07.6 (temporomandibular joint disorders)). Participants who had histories of two or more clinical visits presenting with TMJD were included [9,12].…”
Section: Definition Of Temporomandibular Joint Disorder (Independent Variable)mentioning
confidence: 99%
“…It results in problems in the oral preparatory phase with solid (33%) and liquid (28%) swallowing [8]. TMD can cause headaches, neck pain, body pain, and dietary problems [9,10]. It has also been reported that TMD can cause weight loss (26%) [8].…”
Section: Introductionmentioning
confidence: 99%